Examining strategies for reducing cell phone use while driving: investigating the potential of targeting non-driving participants of cell phone conversations and testing the utility of techniques for reducing habitual responses to cell phones - Miller, Megan Michelle (Kansas State University, 2014)
The current research investigated strategies to reduce cell phone use while driving. Anti-distracted driving campaigns, which typically communicate risk information and target driver behavior, may produce limited effects because people tend to underestimate their risk from this behavior (e.g., Schlehofer et al., 2010). Study 1 compared the effects of messages targeting drivers to messages targeting non-drivers in order to examine the potential of discouraging people from having cell phone communication with others who are driving. Some anti-distracted driving campaigns have emphasized the potential harm to both the driver and others, but whether one approach (self-oriented or other-oriented messaging) is more persuasive than the other has not been examined empirically. Study 1 compared messages that were self-oriented, other-oriented, or neutral in terms of who could be affected by cell phone use while driving. Although cell phone use while driving generally is perceived as dangerous, people may make justifications for engaging in the behavior on at least some occasions, and these justifications may override the influence of risk knowledge on behavior. Consistent with inoculation theory (McGuire, 1961), if given the opportunity to practice refuting these justifications in a controlled setting, people will be more likely to defend themselves against justifications to engage in cell phone use while driving. Thus, Study 1 tested the prediction that participation in an inoculation task would reduce the likelihood of cell phone use while driving. Results from Study 1 suggested an advantage of targeting non-driving participants of cell phone conversations to enhance efforts for reducing on-the-road cell phone use. Study 1 also demonstrated a positive effect of inoculation, but primarily for behavior of non-driving participants of cell phone conversations. In addition to overconfidence in ability to avoid risk, habitual tendencies also may impede the influence of risk communication campaigns (Bayer & Campbell, 2012). Study 2 investigated the potential of mindfulness-based and implementation intentions techniques for helping people overcome habitual responses to their cell phone when doing so is inappropriate or inconvenient. Results indicated that pairing mindfulness-based training with risk information may be significantly more effective than risk information alone at inhibiting inappropriate cell phone use.
Keywords: Cell phone use while driving; Messaging; Temptation resistance; Mindfulness; Implementation intentions; Behavioral Sciences (0602); Experimental Psychology (0623); Social Psychology (0451)